Experiment study investigation compare temperature series circuit and the parallel circuit of thermoelectric and variable water, electrical of thermoelectric for heat exchanger - Akawit Yaidee; Chantana Punlek; Somchai Maneewan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the comparison temperature of thermoelectric (Tec1-12708) between the series circuit and parallel circuit by adjusting of water flow rate pump and electrical supplying to thermoelectric, The electrical voltage at 8,10 and 12 V, water flow rate in reservoir was 0.015 kg/s and 0.025 kg/s. Experiments perform were 6 hours. The result from the researches, thermoelectric with parallel circuit high temperature more than thermoelectric with series circuit. The parallel circuit of thermoelectric can work better than the series circuit in hot side. The different temperature hot side of parallel circuit with the electrical voltage at 8, 10 and 12 V water flow rate in reservoir was 0.015 kg/s temperature average is 22.44 oC, 22.90 oC, 29.86 oC, and water flow rate in reservoir was 0.025 kg/s temperature average is 20.67 oC, 26.66 oC, 27.69 oC. Thermoelectric with parallel circuit makes the higher temperature more than thermoelectric with series circuit about 33%, 37%, 44% water flow rate in reservoir was 0.015 kg/s and 30%, 40%, 41% water flow rate in reservoir was 0.025 kg/s.